18F-FDG PET-CT for Surveillance of Brazilian Patients with Li-Fraumeni Syndrome - Nogueira, Sonia Tereza Santos; Lima, Eduardo Nóbrega Pereira; Nóbrega, Amanda França; Torres, Ivone Do Carmo Gonçalves; Cavicchioli, Marcelo; Hainaut, Pierre; Achatz, Maria Isabel Waddington (Frontiers in Oncology, 2015)
Purpose To evaluate the effectiveness of 18F-Fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT) for detecting early cancer in carriers of germline TP53 mutation, the genetic defect underlying Li-Fraumeni and related syndromes (LFS/LFL) which predisposes to many forms of cancer throughout life. Patients and Methods A total of 30 adult patients from 6 families with germline TP53 mutations were recruited. These patients did not have a diagnosis of cancer in the 24 months preceding the study. Anomalous concentrations from whole-body 18F-FDG-PET/CT were assessed by two independent experts. Suspicious lesions were excised and subjected to pathological examination. Results A total of 6/30 patients showed abnormal 18F-FDG-concentration. Confirmation studies revealed three cases of cancer, including one lung cancer, one ovarian cancer and one disseminated breast cancer. Three patients had non-malignant lesions (one Bartholin’s cyst and two cases of reactive lymph nodes). Conclusions 18F-FDG-PET/CT is effective in detecting cancer in subjects who are asymptomatic according to current screening guidelines. These results further suggest that 18F-FDG-PET/CT is an appropriate method for surveillance of cancer risk in TP53 mutation carriers.